Tinjauan Yuridis Pencabutan Pasal 57 dan Pasal 60 Undang-Undang Nomor 11 Tahun 2006 Tentang Pemerintahan Aceh - Muhammad Heikal Daudy; Fachrurrozi Kaloko (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Article 269 paragraph (3) of Law Number 11 of 2006 on the Government ofAceh (UUPA) states "In the event that a planned amendment to this Law iscarried out by, first consult and has Aceh House of representatives (DPRA) consideration". Revocation of Article 57 and Article 60 of the UUPA through Law Number 7 of 2017 on General Elections by the Indonesian House of Reprsentatives (DPR RI) was not in accordance with the applicable laws and regulations because the DPR RI does not consult and is not based on DPRA considerations as mandated by Article 8 paragraph (2) and Article 269 paragraph (3) of the UUPA, and the impact of losing Aceh's specificity due to the takingover of the authority of the DPRA in recruitment, membership composition, procedures for filling members of the Independent Election Commission (KIP) to the Central KPU as well as the authority in electing members of the Aceh Election Supervisory Committee (Panwaslih) conducted under the UUPA.